HUBUNGAN ANTARA LAMA NYERI PRA OPERASI DENGAN LAMA PERAWATAN POST OPERASI PADA PASIEN APENDISITIS PERFORASI YANG DILAKUKAN LAPAROTOMI APENDEKTOMI DI RSUD DR M HAULUSSY AMBON TAHUN 2018-2019 - Dalia Izma Tuasamu; Is Ikhsan Hataul; Cokorda I A Devi; Ony Wibriyono Angkejaya (Fakultas Kedokteran Universitas Pattimura, 2022)
Perforated appendicitis is a rupture of the appendix which can cause pus to enter the abdominal cavity, causing complications of peritonitis. The delay in establishing a diagnosis has an impact on less than optimal management which in to complications in the form of perforation. This study aims to determine the correlation between the length of preoperative pain and the length of postoperative pain in perforated appendicitis patients who underwent appendectomy laparotomy in RSUD Dr. M. Haulussy Ambon in 2018-2019. The design of this research used an observational analytic method with a cross sectional approach. The research using total sampling technique obtained 42 samples according to the inclusion criteria. Data analysis used univariate analysis and bivariate analysis. The statistical test used was the chi-square test and the alternative test used the fisher's exact test. The results of the chi-square test between the length of preoperative pain and the length of treatment obtained p = 0.041. The conclusion of this study is that there is a significant relationship between the length of preoperative pain and the length of postoperative care in appendicitis patients who underwent appendectomy laparotomy at Dr. M. Haulussy Ambon in 2018-2019.